EVALUATION OF ANTIDIABETIC AND ANTIOXIDANT EFFECTS OF ETHANOLIC LEAF EXTRACT OF ERYTHRINA ABBYSINICA LAM, EX DC - Davie Rexon, Kamadyaapa; Mavuto Masopera, Gondwe; Mathulo, Shauli; Constance, Sewani Rusike; Benedicta, Nkeh Chungag (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was conducted to scientifically evaluate the antidiabetic and antioxidant effects of ethanolic leaf extract of Erythrina abbysinica (EEA). Methods: Acute and sub-chronic effects of EEA at 100, 200, and 400 mg/kg/bwt and glibenclamide (GL) at 5 mg/kg/bwt. were evaluated in both normal and streptozotocin (STZ)-induced diabetic male Wistar rats (250–300 g). The acute studies were performed using oral glucose tolerance test (OGTT). In sub-chronic studies, animals were orally administered with EEA and GL daily for 6 w. Brine shrimp assay was used to determine the toxicity of EEA. 1, 1-diphenyl-2-picrylhydrazyl, ferric reducing capacity of plasma, and thiobarbituric acid reactive substances assays were used to determine antioxidant properties of EEA. Results: Following OGTT, EEA significantly (p<0.05) and dose-dependently (100, 200, and 400 mg/kg/bwt) decreased blood glucose levels in both normal and STZ-induced diabetic rats when compared with positive and negative control counterparts at all-time points, whereas GL significantly (p<0.05) decreased blood glucose only in normal rats but not in diabetic rats. Daily, oral administration of EEA for 6 w significantly (p<0.05) and dose-dependently (100, 200, and 400 mg/kg/bwt) decreased blood glucose levels in STZ-induced diabetic rats when compared with the diabetic control group. EEA revealed weak toxicity with a lethal concentration50 value of 997 μg/ml). Furthermore, EEA showed significant free radical scavenging, total antioxidant, and anti-lipid peroxidative capacities. Conclusion: The study has shed more light on the scientific basis for the use of E. abbysinica in management of diabetes in some communities of Eastern Cape of South Africa.